63. ASSESSMENT OF SURFACE CLEANLINESS QUALITY USING FLUORESCENCE MARKING METHOD AT TWO DEPARTMENTS: DEPARTMENT OF INTERNAL MEDICINE( SERVICE SECTOR) AND DEPARTMENT FOR VIP AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To assess the quality of surface cleanliness using the fluorescence marking method before and after the intervention of training cleaning staff at two clinical departments of Thong Nhat Hospital.Subject and method: The study used fluorescent markers on surfaces to assess the cleanliness quality before and after the intervention of training staff responsible for environmental cleaning.Results: Before the intervention, the percentage of clean environmental surfaces based on visual observation was 94.5%, while the cleanliness rate using fluorescent marker testing was 47.6%. After the intervention, the percentage of clean surfaces based on visual observation increased to 97%, and the completely clean surface rate using the fluorescent marker method rose to 74.8%. Specifically, the cleanliness of floors increased from 45.5% to 74.3%, bed rails from 51.9% to 75.4%, bedside tables from 42.3% to 76.4%, mirrors from 50% to 77.5%, and dining tables from 55.6% to 71.4%.Conclusion: The solution of using the fluorescence marking method to assess surface cleanliness and the intervention of training staff in the cleaning process at the two departments of Requested Inpatient Care and High-Level Official Treatment has proven highly effective.
Keywords: Surface cleaning; intervention; fluorescence marking; visual inspection; cleaning staff; Thong Nhat Hospital